Analisis Penerapan K3 di Laboratorium dengan Metode Failure Mode and Effect Analysis dan Fault Tree Analysis di PT Mutuagung Lestari - Syarif, Abdul Aziz; Hasibuan, Yetti Meuthia; Nugraha, Alief (Metris: Jurnal Sains dan Teknologi, 2026)
Occupational Health and Safety (OHS) is a critical component in high-risk laboratory environments. This study analyzes the implementation of safety measures in the laboratory of PT Mutuagung Lestari using Failure Mode and Effects Analysis (FMEA) and Fault Tree Analysis (FTA). Accident and incident data from the past year were examined to identify failure modes, root causes, effects, and risk levels. The FMEA results indicate that failure modes with the highest Risk Priority Numbers (RPN), such as gas leaks and electrical short circuits, require immediate corrective action. The FTA further reveals that equipment malfunction and human error are the primary contributors to laboratory accidents. Although several OHS protocols are currently in place, shortcomings remain in equipment maintenance and safety supervision. Recommended improvements include strengthening preventive maintenance, redesigning critical work areas, and enhancing safety training programs. The findings provide actionable insights for developing a more robust OHS management system and offer practical implications for reducing accident risks and improving laboratory operational reliability